Analysis of far-infrared spectral radiance observations of the water vapor continuum in the Arctic. (April 2015) - Fox, Cathryn; Green, Paul D.; Pickering, Juliet C.; Humpage, Neil
Abstract: The Radiative Heating in Underexplored Bands Campaign (RHUBC) took place in Barrow, Alaska, in February and March 2007. During RHUBC, high resolution far-infrared spectra were measured simultaneously and independently by two different spectrometers – the Imperial College Tropospheric Airborne Fourier Transform Spectrometer (TAFTS) and the Atmospheric Radiation Measurement program (ARM) Atmospheric Emitted Radiance Interferometer – Extended Range (AERI-ER). Co-incidental far-infrared downwelling radiance measurements from the two instruments show good agreement within their overlapping wavenumber measurement range (400–550 cm −1 ). Radiance measurements taken using the TAFTS instrument are compared to the current Mlawer–Tobin–Clough–Kneizys–Davies (MT-CKD) version 2.5 water vapor continuum parameterization for the spectral range 350–500 cm −1 (20–29 μm). Simulated values agree with the TAFTS observations within uncertainties, enhancing confidence that MT-CKD 2.5 accurately represents the foreign-broadened water vapor continuum in this crucial spectral region. Highlights: Coincident far-infrared spectra measured by two independent radiometers compared. TAFTS and AERI-ER instruments show good agreement within measurement range overlap. A case study of far-infrared Arctic radiance measurements by the TAFTS instrument. Simulated and observed radiances used to test the MT-CKD water vapor continuum model. Measured TAFTS radiances show agreement with simulations and previous studies.